SR AND C ISOTOPES IN LOWER CAMBRIAN CARBONATES FROM THE SIBERIAN CRATON: A PALEOENVIRONMENTAL RECORD DURING THE CAMBRIAN EXPLOSION - Derry L.A.; Brasier M.D.; Corfield R.M.; Rozanov A.Yu.; Zhuravlev A.Y. (My University, 1994)
We report measurements on a suite of well preserved sedimentary carbonates from Lower Cambrian strata of the Lena River region of Siberia. Stable isotopes and major and trace element chemistry have been used to identify potentially unaltered samples for Sr isotopic measurements. The Sr data define a smooth curve of paleoseawater values from the Tommotian through to the early Middle Cambrian. During the Tommotian-Atdabanian interval, rose rapidly from 0.7081 to 0.7085. The rate of change in Sr ratios decreased during the Botomian but rose to 0.7088 in the late Toyonian to early Middle Cambrian. The rate of increase during the Tommotian-Atdabanian was ca. 0.0001/m.y., comparable to the late Miocene change in seawater Sr. We infer that an interval of enhanced erosion during the ‘Cambrian explosion’ was responsible for this increase. An important source for radiogenic Sr to the oceans may have been erosion of the Pan-African orogenic belt of southern Africa. The rapid change in paleoseawater Sr corresponds with an interval of highly variable marine δ13C values. Model results for the Sr and C isotopic records suggest that the quasi-periodicity in the δ13C record is not a consequence of direct erosional forcing. However, our inference of high erosion rates during the Tommotian-Atdabanian implies enhanced fluxes of nutrient elements such as P to the oceans. Phosphorite deposits and black shale deposition in coeval strata suggest that periods of high marine productivity and anoxia may be in part related to enhanced river dissolved fluxes. Our results thus provide some insight into environmental conditions during the ‘Cambrian explosion.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская